Nanoscale neural network using non-linear spin-wave interference - Ádám Papp (Nature Portfolio, 2021)
Wave based computing has sparked much interest for neuromorphic computing due to the inherent interconnectedness of such wave based approaches. Here, Papp, Porod and Csaba show how neural networks can be implemented using spin-waves, taking advantage of spin-waves intrinsic non-linearity.